Negative electrode modification method for modifying surface morphology of magnesium metal negative electrode and application
By forming a network of magnesium fluoride and magnesium borate nanosheets on the surface of magnesium metal anode, the problems of uneven magnesium ion deposition and dendrite growth in magnesium metal batteries are solved, improving electrochemical performance and mechanical stability. This method is suitable for high current density and high capacity conditions and simplifies the production process.
Patent Information
- Application Number
- CN202511948726.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-23
- Publication Date
- 2026-03-20
AI Technical Summary
Magnesium metal anodes in rechargeable metal batteries suffer from problems such as uneven magnesium ion deposition, dendrite growth, and short cycle life. Existing modification methods are complex, costly, and difficult to mass-produce in large sizes.
By using ammonium fluoroborate to dissolve and generate hydrofluoric acid and boric acid, which react with the magnesium metal surface to form a nanosheet network of inorganic components such as magnesium fluoride and magnesium borate, an insulating nanosheet network is constructed, thereby optimizing the surface morphology of the magnesium metal anode.
It achieves uniform deposition of magnesium ions, suppresses dendrite growth, improves electrochemical performance and mechanical stability, and is suitable for reversible exfoliation deposition under high current density and high capacity conditions, simplifying the production process.
Smart Images

Figure CN121709550A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rechargeable metal battery materials technology, specifically to a method and application of modifying the surface morphology of a magnesium metal anode. Background Technology
[0002] For understanding the technical content of this invention: The rapid growth in demand for renewable energy has posed significant challenges to existing energy storage technologies. Rechargeable metal batteries, with their high theoretical capacity and low redox potential, are promising candidates for achieving high-energy-density power batteries. Magnesium metal has attracted considerable attention due to its high abundance, high volumetric energy density, and ease of processing. However, practical research has revealed several key challenges with magnesium metal anodes, making it difficult for the energy density (based on the total mass of the positive and negative electrodes) of magnesium metal batteries to exceed 100 Wh / kg. -1 Magnesium ions (Mg 2+ Magnesium metal anodes have high charge density and strong solvation properties in electrolytes, resulting in slow and uneven deposition kinetics, especially under high current density and high capacity operating conditions, which will exacerbate dendrite growth. Dendrites may puncture the battery separator, causing short circuits between the positive and negative electrodes and leading to safety hazards. At the same time, the repeated growth and fracture of dendrites will consume electrolyte and active materials, thereby shortening the battery cycle life. In order to improve the electrochemical performance of magnesium metal anodes, a variety of anode modification strategies have been adopted. (1) Alloying modification can, to a certain extent, inhibit the formation of passivation layer and enhance the performance of Mg 2+ Kinetics, but the resulting highly active surface often accelerates the side reaction process, thickens the solid electrolyte interphase (SEI) layer and hinders ion transport, especially at high current densities. (2) Three-dimensional current collector design provides a new perspective by reducing local current density, but potential inhomogeneity can lead to local dendrite growth at high rates. (3) Electrolyte additives can suppress side reactions and homogenize the deposition process by adjusting the physicochemical properties and ion transport behavior of the electrode / electrolyte interface. However, the solid-liquid interface layer is not stable enough and may hinder ion conduction. Nucleation uniformity is the core factor that determines the morphology of metal deposition, and its essence lies in the "spatial consistency" of nucleation site distribution, ion flow and interface interaction. The aforementioned methods are difficult to guarantee this "spatial consistency" to a significant extent, so under harsh conditions (current density > 10 mA cm⁻¹), -2 The effect was not satisfactory. Therefore, under practical application conditions (positive electrode mass load > 12 mg / cm³), the effect was not satisfactory. -2 Achieving dendrite-free magnesium anodes remains a major challenge for magnesium metal batteries.
[0003] Relevant patent documents retrieved: This document, published in China (CN117727879A) on March 19, 2024, discloses an MXene-modified magnesium metal anode, its preparation method, and a magnesium metal battery, relating to the field of magnesium metal battery technology. The method involves first placing a polished magnesium foil in a well-dispersed MXene suspension (0.1-10 mg / mL) for a surface reaction for 1-90 minutes, followed by washing and vacuum drying to obtain an MXene-modified magnesium metal anode. This MXene-modified layer effectively inhibits the decomposition of liquid electrolyte on the surface of the magnesium metal anode and reduces the formation of a passivation layer.
[0004] This document, published in China (CN118693250A) on September 24, 2024, discloses a fluoride-ion battery, a negative electrode active material for the fluoride-ion battery, and a method for manufacturing the same, providing a fluoride-ion battery capable of achieving high charge-discharge capacity. The fluoride-ion battery of this document has a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer formed between the positive and negative electrode active material layers. The negative electrode active material layer of the fluoride-ion battery contains metallic magnesium, magnesium fluoride, and calcium barium fluoride, with a mass ratio of metallic magnesium to magnesium fluoride of 0.1-10.0.
[0005] This document, published in China (CN119101972A) on December 10, 2024, discloses a method for preparing an MXene@zIF-67 composite coating on the negative electrode surface of a magnesium battery. The method includes: polishing, cleaning, drying, and degreasing a magnesium alloy substrate; etching Ti3AlC2 with hydrofluoric acid to obtain MXene powder; dissolving the MXene powder and cobalt nitrate hexahydrate in methanol as solution A; dissolving 2-methylimidazole solution in methanol as solution B; pouring solution A into solution B and adding hexadecyltrimethylammonium bromide to obtain MXene@zIF-67 powder; dissolving the powder in methanol; using graphite as the anode and the degreased magnesium alloy as the cathode; applying a constant voltage, removing the magnesium cathode sheet, and drying it to obtain the MXene@zIF-67 composite coating. This composite coating can reduce the voltage hysteresis and electrochemical impedance of the magnesium battery, improve the discharge voltage plateau, and enhance the overall discharge performance of the magnesium battery.
[0006] Relevant non-patent literature retrieved: The journal *Acta Metallurgica Sinica*, the article titled "Research Progress on Anode Materials and Interface Chemistry for Rechargeable Magnesium Batteries," Volume 3, published on January 22, 2025, discloses current research progress in addressing the passivation problem of pure Mg anodes. This progress involves two main approaches: firstly, designing non-magnesium-based anode materials, such as alloy anodes based on Group IIIA, IVA, and VA elements, as a viable option; and secondly, designing three-dimensional magnesium-loving structures, such as graphitic carbon nanosubstrates (GC-NSs), three-dimensional MoSe2, three-dimensional Mg3Bi2, amorphous MgO-encapsulated Zn framework, and vertically aligned nickel hydroxide nanosheet arrays (Ni(OH)2@CC) on carbon cloth, to circumvent uneven Mg deposition / exfoliation and perforation issues. These studies demonstrate the significant importance of anode material and interface structure and composition design. The solid electrolyte interphase (SEI), as a key interfacial layer between the negative electrode material and the electrolyte, plays a crucial role in ion conduction, electrode structure stability, and battery cycle life. With the rapid development of ion battery technology, SEI research has become one of the core focuses for optimizing battery performance and ensuring battery safety and reliability. By precisely controlling the chemical composition, microstructure, and formation process of the SEI film, the aim is to construct battery systems with superior performance.
[0007] The prior art represented by the aforementioned documents has at least the following unresolved technical problems or defects: (1) The preparation process is complex and the process parameters are strictly controlled. The relevant evidence is: CN119101972A, which requires three core processes: MXene etching, in-situ synthesis of MXene@ZIF-67 composite material, and cathodic electrophoretic deposition. Each step contains multiple subdivision operations. Furthermore, the requirements for material ratio (such as the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazolium needs to be precisely controlled at 1:4-1:12), voltage (10-60V), and electrophoretic spacing (2-4cm) are extremely high. Slight deviations will lead to defects in the coating structure. (2) There are many types of raw materials and the cost is high. The relevant evidence is: Publication No. CN119101972A. This document requires the use of a variety of special chemicals such as Ti3AlC2 (aluminum carbide), cobalt nitrate hexahydrate, 2-methylimidazole, and hexadecyltrimethylammonium bromide. Among them, Ti3AlC2 and MXene powder are expensive. (3) The equipment requirements are complex and large-scale production is difficult. The relevant evidence is: Publication No. CN119101972A. The technical solution in this document requires special equipment such as ultrasonic equipment, voltage regulator, and high-speed centrifuge (5000-10000r / min). The multi-step process and precise parameter control make it difficult to achieve the batch preparation of large-size magnesium anodes.
[0008] In solving the above problems or overcoming the above defects, the present invention encountered the following difficulties and obstacles: When characterizing the negative electrode after cycling, the diaphragm tends to stick to the negative electrode side. Summary of the Invention
[0009] The purpose of this invention is to provide: A method for modifying the surface morphology of magnesium metal anodes, and related technologies, to solve technical problems such as uneven magnesium ion deposition, dendrite growth, short cycle life, or combinations thereof.
[0010] Terminology Explanation: Unless otherwise defined, all technical terms in this document have the same meanings as commonly understood by one of ordinary skill in the art to which the subject matter of the claims pertains. Unless otherwise stated, all patents, patent inventions, and publications cited in this document are incorporated herein by reference in their entirety. If multiple definitions exist for terms in this document, the definitions in this chapter shall prevail.
[0011] It should be understood that the above brief description and the following detailed description are exemplary and for illustrative purposes only, and do not limit the subject matter of the invention in any way. In this invention, the singular is used in conjunction with the plural unless otherwise specifically stated. It should also be noted that, unless otherwise stated, the use of “or” or “or” means “and / or”. Furthermore, the use of the term “comprising” and other forms such as “including,” “containing,” and “contains” are not limiting.
[0012] Definitions of standard chemical terms can be found in the references "Interpretation of GB / T 46314-2025 Terminology Standard for Primary Battery Materials", "Interpretation of Standard for Technical Specifications of Liquid Metal Energy Storage Battery Cells", "Metal-Air Batteries: Fundamentals and Applications", and "Advanced Technologies for Rechargeable Batteries".
[0013] Unless otherwise stated, conventional methods within the scope of the art, such as electron microscopy analysis, scanning electron microscopy (SEM), etc., shall be used.
[0014] Unless specifically defined herein, the use of all commercially available products herein employs standard techniques. For example, it may be carried out using the manufacturer's instructions for use with the kit, or in accordance with methods known in the art or the description of this invention. The techniques and methods described herein can generally be implemented according to conventional methods well known in the art, based on the descriptions in the various summary and more specific documents cited and discussed in this specification.
[0015] The terms "ammonium fluoroborate" and "NH4BF4" used in this article refer to: an inorganic compound in the field of chemistry, a white crystalline powder with the chemical formula NH4BF4, composed of ammonium ions (NH4+). + ) and fluoroborate ions (BF4) - It is composed of ⁻, readily soluble in polar solvents such as water and methanol, and its aqueous solution is weakly acidic. It exhibits good thermal stability, but decomposes at high temperatures (approximately 230°C) to produce products such as boron fluoride and ammonia. It combines the typical characteristics of ionic compounds with the stable structure of fluoroborate.
[0016] The term "magnesium metal anode" as used in this article refers to the core component of a magnesium metal battery, specifically the battery anode that uses metallic magnesium (Mg) as the active material, through the oxidation reaction of magnesium (Mg-2e). - →Mg 2+ Magnesium oxide (MgO) is a key electrode material for realizing high-energy-density magnesium batteries. It releases electrons to provide electrical energy to the battery.
[0017] The term "oxide layer" used in this article refers to a thin film formed on the surface of a material by a chemical reaction with oxygen. It is an oxide layer formed when surface atoms of metals, alloys, or semiconductors combine with oxygen in air, water, or other oxygen-containing environments, and has a dual function of protecting the substrate or affecting the material's properties.
[0018] The term "surface morphology modification" used in this article refers to the core technology in the fields of materials surface engineering and materials science, which uses physical, chemical, or composite processes to directionally control the microscopic geometry of a material surface (such as roughness, pore structure, protrusion / concavity features, etc.) in order to optimize the surface properties of the material or endow it with new functions.
[0019] The term "H3BO3" used in this article refers to boric acid, a weakly acidic inorganic compound, also known as orthoboric acid. It is a white crystalline powder or scaly crystal, an important oxyacid of boron, readily soluble in hot water and glycerol, slightly soluble in cold water, and its aqueous solution is weakly acidic. It has good thermal stability; when heated above 100℃, it gradually dehydrates to form metaboric acid and tetraboric acid, eventually decomposing into boron trioxide. In magnesium metal batteries, it is commonly used as an electrolyte additive to regulate the electrolyte pH, participate in the construction of a stable electrode / electrolyte interface film, and inhibit the oxidative corrosion of the magnesium anode. It is also used as a raw material in the preparation of compounds such as ammonium fluoroborate.
[0020] The term "HF" used in this article refers to hydrofluoric acid, composed of hydrogen and fluorine elements. At room temperature, it is a colorless gas with a pungent odor. Its aqueous solution is hydrofluoric acid, the only acid that can react with silicon dioxide. It is highly corrosive (especially to skin and bones) and toxic, requiring strict protection. Its aqueous solution is weakly acidic (due to low ionization caused by hydrogen bonding), but its corrosiveness is far stronger than that of ordinary weak acids. It can react with most metals and metal oxides to form fluorides. It can be used to prepare fluoroboric acid (as a fluorine source) and to etch oxide layers on metal surfaces. In battery material processing, it can assist in the preparation of porous magnesium anodes (light etching).
[0021] The term "Mg3(BO3)2" used in this article refers to magnesium borate, a white crystalline powder belonging to the borate class of substances. It is sparingly soluble in water, chemically stable, and has a high melting point. It possesses excellent high-temperature resistance and corrosion resistance. In magnesium metal batteries, it may be a product of electrode interface reactions (such as when the electrolyte contains borate ions). The resulting magnesium borate film can affect interfacial impedance and stability. It is also used in ceramics, flame retardant materials, lubricants, and other fields.
[0022] The term "MgF2" used in this article refers to magnesium fluoride, a white powdery crystal, a typical ionic fluoride, sparingly soluble in water and most organic solvents, with extremely high chemical stability, low refractive index, and good light transmittance. In magnesium metal batteries, it is often used as a core component of the electrode interface protective film (such as when the electrolyte contains fluorine additives). Magnesium fluoride films are dense, have moderate conductivity, and can inhibit magnesium dendrite growth and reduce interfacial impedance; it is also used in optical glass, ceramics, welding flux, and other fields.
[0023] The term "confinement index" used in this article refers to the square of the ratio of the critical nucleation diameter of magnesium ions to the average diameter of the nanosheet mesh (2rcrit / dave). 2 The confinement index describes the strength of the confinement effect of the nanosheet network on magnesium ions. The larger the confinement index, the stronger the confinement effect, and the better the electrochemical performance of the corresponding modified magnesium anode.
[0024] The term "insulating nanosheet network" used in this article refers to an insulating material system with a three-dimensional interconnected structure formed by the physical stacking or chemical interaction of two-dimensional nanosheets (sheet-like materials with a thickness on the nanometer scale and a lateral dimension on the micrometer scale). Its core characteristics are "nanosheet framework + network-like porous structure + insulating properties." In magnesium metal batteries, it can serve as a surface modification layer for the negative electrode, utilizing its insulating properties to suppress dendrite growth while simultaneously ensuring ion transport through its network pores, thus improving battery cycle stability.
[0025] The term "average pore size" used in this article refers to a key parameter characterizing the degree of pore size concentration in porous materials. It is the statistical average of the equivalent diameters of all pores in a porous material, used to quantify the overall size level of the pores. In battery electrode materials (such as porous magnesium anodes and separators), the average pore size needs to match the ion transport requirements (typically tens to hundreds of nanometers). If it is too large, it will reduce the specific surface area; if it is too small, it may hinder ion diffusion.
[0026] In a first aspect, the present invention provides: a method for modifying the surface morphology of a magnesium metal anode, comprising the steps of: (1) Remove the oxide layer from the magnesium metal anode to obtain the treated magnesium metal; (2) Dissolve ammonium fluoroborate in water to obtain an ammonium fluoroborate solution; (3) The magnesium metal obtained in step (1) is reacted with the ammonium fluoroborate solution obtained in step (2) to obtain the modified magnesium metal anode with the modified surface morphology.
[0027] The technical features include: ammonium fluoroborate, water, and an oxide layer.
[0028] The reaction mechanism is as follows: NH4BF4 + 3H2O → NH4F + H3BO3 + 3HF 2H3BO3 + 3Mg → Mg3(BO3)2 + 3H2 2HF + Mg → MgF₂ + H₂ The form of the magnesium metal negative electrode includes, but is not limited to, at least one of sheet, foil, block, and filament. The shape of the magnesium metal negative electrode is preferably at least one of sheet or foil; The shape of the magnesium metal negative electrode is further preferably foil-shaped; Preferably, the shape of the foil-shaped magnesium metal negative electrode includes, but is not limited to, at least one of circular, rectangular, and porous shapes; More preferably, the shape is circular; More preferably, the foil-shaped magnesium metal negative electrode is circular with a diameter of 1 cm; The method for removing the oxide layer is selected from at least one of physical removal, acid etching, alkaline cleaning, and organic solvent soaking; The preferred method for removing the oxide layer is at least one of physical removal and acid etching. The preferred method for removing the oxide layer is physical removal. Preferably, the physical removal includes mechanical grinding and mechanical polishing. More preferably, the grit of the sandpaper used for mechanical polishing is selected from 400-5000 grit; More preferably, the grit of the sandpaper used for mechanical polishing is selected from 600-2000 grit; Most preferably, the mechanical polishing is performed by sequentially polishing with 600-grit, 1000-grit, and 2000-grit sandpaper; More preferably, the mechanical polishing method includes, but is not limited to, at least one of wet polishing, dry polishing, metallographic polishing machine polishing, and ultrasonic-assisted mechanical polishing; More preferably, the mechanical polishing method is metallographic polishing.
[0029] The water includes, but is not limited to, at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; The water is preferably at least one of purified water, deionized water, and distilled water; The water is further preferably deionized water; Preferably, the concentration of the ammonium fluoroborate solution obtained in step (2) is 1wt%-5wt%; More preferably, the concentration of the ammonium fluoroborate solution is 1wt%-3wt%; More preferably, the concentration of the ammonium fluoroborate solution is 2 wt%; The reaction temperature in step (3) is 10-30℃; The preferred reaction temperature in step (3) is 25°C; The reaction time in step (3) is 1-10 min; The preferred reaction time in step (3) is 5 minutes; Preferably, the reaction in step (3) is followed by a washing and drying step; More preferably, the solvent used for cleaning is water; More preferably, the water includes, but is not limited to, at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; Most preferably, the water is deionized water; More preferably, the drying method includes, but is not limited to, at least one of freeze drying, spray drying, oven drying, air drying, blow drying, natural drying, and vacuum drying; More preferably, the drying method is oven drying; More preferably, the drying temperature is 30-60℃; most preferably, it is 40℃. More preferably, the drying time is 1-3 hours; most preferably, it is 2 hours.
[0030] Preferably, the method for modifying the surface morphology of the magnesium metal anode includes the following steps: (1) The magnesium metal anode was polished in sequence with sandpaper of different mesh sizes (600 mesh, 1000 mesh, 2000 mesh) to remove the natural oxide layer; (2) Apply transparent tape to one side of the magnesium foil processed in step (1) and cut it into a circle with a diameter of 1cm; (3) Dissolve the solid ammonium fluoroborate in a centrifuge tube containing deionized water, and attach double-sided tape to the inner cover of the centrifuge tube. Fix the metal negative electrode disc with transparent tape attached to one side obtained in step (2) to the inner cover of the centrifuge tube. (4) Invert the centrifuge tube to allow the 2wt% ammonium fluoroborate solution to react with the magnesium anode for 5 minutes. (5) Soak the magnesium metal anode after the reaction repeatedly with deionized water and absorb the residual moisture on the surface with dust-free paper, and then place it in a 40℃ oven for vacuum drying for 2 hours.
[0031] Based on further solutions to the technical problems of the present invention, or simultaneous solutions to multiple technical problems, the preferred solution in the technical solution provided in the first aspect of the present invention includes: The first preferred embodiment: the shape of the foil-shaped magnesium metal negative electrode includes, but is not limited to, at least one of circular, rectangular, and porous shapes; preferably circular; more preferably circular with a diameter of 1 cm. This technical solution, based on solving the technical problem of "improving electrochemical performance and mechanical stability", further solves the technical problem of "further improving electrochemical performance and mechanical stability".
[0032] The second preferred solution involves removing the oxide layer using at least one of physical removal, acid etching, alkaline cleaning, and organic solvent immersion; preferably, at least one of physical removal and acid etching; more preferably, physical removal; preferably, the physical removal includes mechanical grinding and mechanical polishing; even more preferably, the sandpaper grit used for mechanical grinding is selected from 400-5000 grit; even more preferably, the sandpaper grit used for mechanical grinding is selected from 600-2000 grit; most preferably, the mechanical grinding is performed sequentially with 600 grit, 1000 grit, and 2000 grit sandpaper. This technical solution, while addressing the technical problem of "improving electrochemical performance and mechanical stability," further addresses the technical problem of "further improving electrochemical performance and mechanical stability."
[0033] The third preferred option is that the concentration of the ammonium fluoroborate solution obtained in step (2) is 1wt%-5wt%; preferably 1wt%-3wt%; and even more preferably 2wt%. This technical solution solves the technical problem of "improving electrochemical performance and mechanical stability" and further solves the technical problem of "further improving electrochemical performance and mechanical stability".
[0034] The fourth preferred option is that the reaction temperature in step (3) is 10-30℃, preferably 25℃; and the reaction time in step (3) is 1-10 min, preferably 5 min. This technical solution solves the technical problem of "improving electrochemical performance and mechanical stability" and further solves the technical problem of "further improving electrochemical performance and mechanical stability".
[0035] The fifth preferred option: the drying method includes, but is not limited to, at least one of freeze drying, spray drying, oven drying, air drying, blow drying, natural drying, and vacuum drying; preferably, oven drying; more preferably, the drying temperature is 30-60℃; most preferably, 40℃; even more preferably, the drying time is 1-3 hours; most preferably, 2 hours. This technical solution, based on solving the technical problem of "improving electrochemical performance and mechanical stability," further solves the technical problem of "further improving electrochemical performance and mechanical stability."
[0036] Secondly, the present invention provides: a magnesium metal anode with surface morphology modified according to the above-mentioned anode modification method, wherein a uniform and continuous insulating nanosheet network is formed on the surface of the magnesium metal anode, with an average pore size of less than 125 nm.
[0037] Among its technical features are: an insulating nanosheet network and an average pore size.
[0038] Preferably, the average pore size is less than 90 nm; More preferably, the average pore size is less than 80 nm; More preferably, the average pore size is 68.95 nm.
[0039] Thirdly, the present invention provides the application of the above-mentioned negative electrode modification method in magnesium metal battery materials.
[0040] This includes the application of anode modification methods as a technical feature.
[0041] Preferably, the application involves the hydrolysis of ammonium fluoroborate in water to produce hydrofluoric acid (HF) and boric acid (H3BO3), which then react with Mg... 2+ By self-assembling magnesium fluoride, magnesium borate, and other inorganic-rich nanosheet networks onto the magnesium metal surface, these structures possess electronic insulation, ionic insulation, and mechanical stability. The uniformly distributed nanoscale mesh not only homogenizes the magnesium ion flux but also effectively inhibits chloride ion accumulation, preventing self-accelerated corrosion and achieving Mg… 2+ Uniform stripping and deposition, and record-breaking reversible stripping deposition at high current density / high capacity.
[0042] Fourthly, the present invention provides an alternative to the above-described negative electrode modification method, comprising the steps of: (1) Remove the oxide layer from the magnesium metal anode to obtain the treated magnesium metal; (2) Dissolve HF or H3BO3 in water to obtain a reaction solution; (3) The magnesium metal obtained in step (1) is reacted with the reaction solution obtained in step (2) to obtain the modified magnesium metal anode with the modified surface morphology.
[0043] Among them are the technical features: HF and H3BO3.
[0044] The reaction mechanism is as follows: 2H3BO3 + 3Mg → Mg3(BO3)2 + 3H2 2HF + Mg → MgF₂ + H₂ The form of the magnesium metal negative electrode includes, but is not limited to, at least one of sheet, foil, block, and filament. The shape of the magnesium metal negative electrode is preferably at least one of sheet or foil; The shape of the magnesium metal negative electrode is further preferably foil-shaped; Preferably, the shape of the foil-shaped magnesium metal negative electrode includes, but is not limited to, at least one of circular, rectangular, and porous shapes; More preferably, the shape is circular; More preferably, the foil-shaped magnesium metal negative electrode is circular with a diameter of 1 cm; The method for removing the oxide layer is selected from at least one of physical removal, acid etching, alkaline cleaning, and organic solvent soaking; The preferred method for removing the oxide layer is at least one of physical removal and acid etching. The preferred method for removing the oxide layer is physical removal. Preferably, the physical removal includes mechanical grinding and mechanical polishing. More preferably, the grit of the sandpaper used for mechanical polishing is selected from 400-5000 grit; More preferably, the grit of the sandpaper used for mechanical polishing is selected from 600-2000 grit; Most preferably, the mechanical polishing is performed by sequentially polishing with 600-grit, 1000-grit, and 2000-grit sandpaper; More preferably, the mechanical polishing method includes, but is not limited to, at least one of wet polishing, dry polishing, metallographic polishing machine polishing, and ultrasonic-assisted mechanical polishing; More preferably, the mechanical polishing method is metallographic polishing.
[0045] The water includes, but is not limited to, at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; The water is preferably at least one of purified water, deionized water, and distilled water; The water is further preferably deionized water; Preferably, the concentration of the reaction solution obtained in step (2) is 1wt%-5wt%; More preferably, the concentration of the reaction solution is 1wt%-3wt%; More preferably, the concentration of the reaction solution is 2 wt%; The reaction temperature in step (3) is 10-30℃; The preferred reaction temperature in step (3) is 25°C; The reaction time in step (3) is 1-10 min; The preferred reaction time in step (3) is 5 minutes; Preferably, the reaction in step (3) is followed by a washing and drying step; More preferably, the solvent used for cleaning is water; More preferably, the water includes, but is not limited to, at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; Most preferably, the water is deionized water; More preferably, the drying method includes, but is not limited to, at least one of freeze drying, spray drying, oven drying, air drying, blow drying, natural drying, and vacuum drying; More preferably, the drying method is oven drying; More preferably, the drying temperature is 30-60℃; most preferably, it is 40℃. More preferably, the drying time is 1-3 hours; most preferably, it is 2 hours.
[0046] Examples 1-4 of this invention at least support the protection scope of the technical features "ammonium fluoroborate", "oxide layer" and "water".
[0047] The technical feature "ammonium fluoroborate" is derived from the aforementioned explanation and / or the corresponding technical features in Examples 1-4, such as "the concentration of the obtained ammonium fluoroborate solution is 1wt%-5wt%; more preferably, the concentration of the ammonium fluoroborate solution is 1wt%-3wt%; even more preferably, the concentration of the ammonium fluoroborate solution is 2wt%", and is summarized from the common feature "an inorganic compound in the chemical field, a white crystalline powder with the chemical formula NH4BF4". Therefore, those skilled in the art can reasonably presume that the technical feature "ammonium fluoroborate", its subordinate concepts, its essentially equivalent technical means, and technical means that can replace "ammonium fluoroborate" based on existing technology and conventional technical means and common knowledge, should all fall within the protection scope of the technical feature "ammonium fluoroborate". For example, replacing "ammonium fluoroborate" with "hydrofluoric acid", "boric acid", etc., while keeping other technical features unchanged, still falls within the protection scope of the technical feature "ammonium fluoroborate".
[0048] The technical feature "oxide layer" is derived from the common feature "thin film formed by the chemical reaction between the material surface and oxygen" in the foregoing explanation and / or the corresponding technical feature "removal of oxide layer from magnesium metal negative electrode" in Examples 1-4. Therefore, those skilled in the art can reasonably presume that the technical feature "oxide layer," its subordinate concepts, its substantially equivalent technical means, and technical means that can replace "oxide layer" based on existing technology and conventional technical means and common knowledge should all fall within the protection scope of the technical feature "oxide layer." For example, replacing "oxide layer" with "oxidizing substance" while keeping other technical features unchanged still falls within the protection scope of the technical feature "oxide layer."
[0049] The technical feature "water" is summarized from the foregoing explanation and / or the corresponding technical feature in Examples 1-4, such as "the water includes, but is not limited to, at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; the water is preferably at least one of purified water, deionized water, and distilled water; the water is further preferably deionized water," etc. Therefore, those skilled in the art can reasonably presume that the technical feature "water," its subordinate concepts, its substantially equivalent technical means, and technical means that can replace "water" within the scope of conventional technical means and common knowledge based on the existing level of technology should all fall within the protection scope of the technical feature "water." For example, replacing "water" with "deionized water," "purified water," etc., while keeping other technical features unchanged, still falls within the protection scope of the technical feature "water."
[0050] In this invention, Examples 1-4 at least support the protection scope of the technical features "insulating nanosheet network" and "average pore size".
[0051] The technical feature "insulating nanosheet network" is derived from the aforementioned explanation and / or the corresponding technical feature in Examples 1-4, such as "a uniform and continuous insulating nanosheet network is formed on the surface of the magnesium metal negative electrode," and is summarized by the common feature "an insulating material system with a three-dimensional interconnected structure formed by physical stacking or chemical action of two-dimensional nanosheets (sheet materials with a thickness of nanometers and a lateral size of micrometers). Therefore, those skilled in the art can reasonably presume that the technical feature "insulating nanosheet network," its subordinate concepts, its essentially equivalent technical means, and technical means that can replace "insulating nanosheet network" based on existing technology and conventional technical means and common knowledge should all fall within the protection scope of the technical feature "insulating nanosheet network." For example, replacing "insulating nanosheet network" with "insulating layer," "composite coating," etc., while keeping other technical features unchanged, still falls within the protection scope of the technical feature "insulating nanosheet network."
[0052] The technical feature "average pore size" is derived from the aforementioned explanation and / or the corresponding technical features in Examples 1-4, such as "the average pore size is less than 90 nm; more preferably, the average pore size is less than 80 nm; and even more preferably, the average pore size is 68.95 nm," through the common feature "the statistical average of the equivalent diameters of all pores in the porous material, used to quantify the overall size level of the pores." Therefore, those skilled in the art can reasonably infer that the technical feature "average pore size," its subordinate concepts, its essentially equivalent technical means, and technical means that can replace "average pore size" within the scope of conventional technical means and common knowledge based on the existing technical level should all fall within the protection scope of the technical feature "average pore size." For example, replacing "average pore size" with "pore" or "pore diameter" while keeping other technical features unchanged still falls within the protection scope of the technical feature "average pore size."
[0053] In this invention, embodiments 1-4 at least support the protection scope of the technical feature "application of negative electrode modification method".
[0054] The technical feature “application of negative electrode modification method” is explained above and / or the corresponding technical feature in Examples 1-4: “Ammonium fluoroborate hydrolyzes in water to produce hydrofluoric acid (HF) and boric acid (H3BO3), which react with Mg…” 2+ By self-assembling magnesium fluoride, magnesium borate, and other inorganic-rich nanosheet networks onto the magnesium metal surface, these structures possess electronic insulation, ionic insulation, and mechanical stability. The uniformly distributed nanoscale mesh not only homogenizes the magnesium ion flux but also effectively inhibits chloride ion accumulation, preventing self-accelerated corrosion and achieving Mg… 2+The phrase "uniform peeling and deposition, and record-breaking reversible peeling and deposition under high current density / high capacity" is summarized as follows. Therefore, those skilled in the art can reasonably presume that the technical feature "application of negative electrode modification method", its subordinate concepts, its basically equivalent technical means, and technical means that can replace it within the scope of conventional technical means and common knowledge based on the existing technical level should all fall within the protection scope of the technical feature "application of negative electrode modification method".
[0055] The beneficial effects of this invention are as follows: The present invention has at least the following beneficial effects: (1) The ammonium fluoroborate used in this invention hydrolyzes in water to produce hydrofluoric acid (HF) and boric acid (H3BO3), which react with Mg 2 + By self-assembling magnesium fluoride, magnesium borate, and other inorganic-rich nanosheet networks onto the magnesium metal surface, these structures possess electronic insulation, ionic insulation, and mechanical stability. The uniformly distributed nanoscale mesh not only homogenizes the magnesium ion flux but also effectively inhibits chloride ion accumulation, preventing self-accelerated corrosion and achieving Mg… 2+ Uniform stripping and deposition, and record-breaking reversible stripping deposition at high current density / high capacity.
[0056] (2) The magnesium anode with a special morphology described in this invention also has scalability. Similarly, we treated the magnesium anode with HF, H3BO3, and a mixture thereof with the same pH for the same amount of time, and all obtained morphological characteristics similar to those obtained with NH4BF4 solution treatment. More importantly, compared with the magnesium anode before treatment, all of them obtained better electrochemical performance. Based on this, we proposed the concept of confinement index, which is the square of the ratio of the critical nucleation diameter of magnesium ions to the average diameter of the nanosheet mesh. The confinement index describes the strength of the confinement effect of the nanosheet network on magnesium ions. The larger the confinement index, the stronger the confinement effect, and the better the electrochemical performance of the corresponding modified magnesium anode.
[0057] (3) The present invention is simple and efficient to operate, and can easily realize the mass production of large-size magnesium anodes. At the same time, it has good air stability. After the treated magnesium foil is placed in the air for 5 days, its performance is not significantly different from that when it is not placed in the air. Therefore, it has high practical application value.
[0058] (4) Compared with the prior art, the present invention provides a technical solution with a different technical concept, and its technical effect is equivalent to or slightly improved with the prior art. The difference between the technical concept of the present invention and the prior art includes, but is not limited to, "utilizing ammonium fluoroborate in water to hydrolyze to generate hydrofluoric acid (HF) and boric acid (H3BO3), which, together with Mg..." 2+"Forming nanosheet networks rich in inorganic components such as magnesium fluoride and magnesium borate on the surface of magnesium metal through self-assembly", etc. Attached Figure Description
[0059] Figure 1 This is a surface morphology diagram of the FB-Mg anode.
[0060] Figure 2 This is a diagram showing the pore diameter distribution of the nanosheet network on the surface of the FB-Mg anode.
[0061] Figure 3 3 mA cm -2 / 3 mAh cm -2 The voltage-time curve of FB-Mg under the given conditions.
[0062] Figure 4 A comparison of the full-cell performance of FB-Mg and high-loading Mo6S8 cathode materials matched with unmodified magnesium anodes.
[0063] Figure 5 This is a surface morphology diagram of the HF-Mg negative electrode.
[0064] Figure 6 This is a diagram showing the pore diameter distribution of the nanosheet network on the surface of the HF-Mg anode.
[0065] Figure 7 3 mA cm -2 / 3 mAh cm -2 Voltage-time curve of HF-Mg under the given conditions.
[0066] Figure 8 This is a surface morphology diagram of the HBO-Mg negative electrode.
[0067] Figure 9 This is a diagram showing the pore diameter distribution of the nanosheet network on the surface of the HBO-Mg anode.
[0068] Figure 10 3 mA cm -2 / 3 mAh cm -2 The voltage-time curve of HBO-Mg under the given conditions.
[0069] Figure 11 The image shows the surface morphology of the mix-Mg anode.
[0070] Figure 12 This is a diagram showing the pore diameter distribution of the nanosheet network on the surface of the mix-Mg anode.
[0071] Figure 13 3 mA cm -2 / 3 mAh cm -2 Voltage-time curves of mix-Mg under the given conditions.
[0072] Figure 14 The graph shows the surface energy-voltage-time curve of the Mg anode before modification.
[0073] Figure 15 The graph shows the overpotential-voltage-time curves of the Mg anode before modification.
[0074] Figure 16 The images show the contact angle test results of the Mg anode before and after modification. Detailed Implementation
[0075] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the invention in any way. The following content is merely an exemplary description of the scope of protection claimed by the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, and such changes should also fall within the scope of protection claimed by the present invention.
[0076] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all instruments, devices, equipment, reagents, products, etc., used in the embodiments of the present invention are obtained through conventional commercial means.
[0077] Specific raw material information is shown in Table 1: Table 1. Raw Material Information
[0078] Example 1 This embodiment provides a method for modifying the surface morphology of magnesium metal to achieve stable cycling of the negative electrode. The method includes the following steps: (1) Use sandpaper of different grits (600 grit, 1000 grit, 2000 grit) to repeatedly polish the magnesium foil to remove the dull oxide surface and expose the fresh silvery-white magnesium metal. Then, stick one side of the foil tightly with transparent glue and cut it into a round piece with a diameter of 10 mm. (2) Dissolve 0.2 g of ammonium fluoroborate (NH4BF4) solid in a centrifuge tube containing 10 mL of deionized water, and attach double-sided tape to the inner cap of the centrifuge tube. Fix the magnesium negative electrode disc with transparent tape attached to one side obtained in step (1) to the inner cap of the centrifuge tube. (3) Invert the centrifuge tube to allow the solution to react fully with the magnesium anode for 5 min; (4) After removing the magnesium anode, the surface of the magnesium anode is repeatedly washed with deionized water to remove the residual solution. After absorbing the residual water on the surface, it is placed in an oven and vacuum dried at 40°C for 2 h to obtain a light yellow FB-Mg anode.
[0079] The obtained FB-Mg anode scanning electron microscope (SEM) image is as follows: Figure 1As shown, a continuous and uniform nanosheet network is distributed on the surface of the FB-Mg anode. The average mesh size distribution is shown in the figure below. Figure 2 As shown, its 3 mA cm -2 / 3 mAh cm -2 The voltage-time curve is as follows Figure 3 As shown. A full cell matching the Mo6S8 cathode material is shown below. Figure 4 As shown in the figure. In summary, the obtained FB-Mg anode exhibits excellent electrochemical performance.
[0080] Example 2 This embodiment provides a method for modifying the surface morphology of magnesium metal to achieve stable cycling of the negative electrode. The method includes the following steps: except that in (2) the solution is changed to an HF solution with equal pH, the other materials and preparation process are the same as in Example 1, and finally an HF-Mg negative electrode is obtained, the SEM of which is shown in Figure 1. Figure 5 As shown, the average mesh size distribution diagram is as follows: Figure 6 As shown, at 3 mA cm -2 / 3 mAhcm -2 The voltage-time curve under the given conditions is as follows Figure 7 As shown.
[0081] Example 3 This embodiment provides a method for modifying the surface morphology of magnesium metal to achieve stable cycling of the negative electrode. The method includes the following steps: except that in (2) the solution is changed to an H3BO3 solution with equal pH, the other materials and preparation process are the same as in Example 1, and finally an HBO-Mg negative electrode is obtained, the SEM of which is shown in Figure 1. Figure 8 As shown in the figure, the average mesh size distribution is as follows: Figure 9 As shown, at 3 mA cm -2 / 3mAh cm -2 The voltage-time curve under the given conditions is as follows Figure 10 As shown.
[0082] Example 4 This embodiment provides a method for modifying the surface morphology of magnesium metal to achieve stable cycling of the negative electrode. The method includes the following steps: except that in (2), the solution is changed to an isopH HF / H3BO3 mixed solution (mixed according to 1.7μL HF liquid / 0.02g boric acid solid), the other materials and preparation process are the same as in Example 1, and finally a mix-Mg negative electrode is obtained, the SEM of which is shown in Figure 1. Figure 11 As shown in the figure, the average mesh size distribution is as follows: Figure 12 As shown, at 3mA cm -2 / 3mAh cm -2 The voltage-time curve under the given conditions is as follows Figure 13 As shown.
[0083] Detection example 1. Surface energy testing - contact angle measurement method When two liquids of known polarity are dropped onto a metal surface, the angle between the droplet and the surface is called the contact angle. The surface energy of the metal surface can be calculated using the Owens formula.
[0084] 2. Overpotential test Overpotential is the difference between the nucleation potential and the voltage plateau at the instant of the first charge and discharge of a symmetrical battery.
[0085] 3. Critical nucleation radius (r) crit )test It is calculated based on existing formulas.
[0086] 4. Average diameter of nanosheet mesh pores (d) ave )test The Nano Measure software measures the diameter of 100 mesh openings and directly provides the average diameter.
[0087] 5. Confinement Index The confinement index is the square of the ratio of the critical nucleation diameter of magnesium ions to the average diameter of the nanosheet mesh.
[0088] Test Example 1: Limiting Index and Cycle Time Test The modified magnesium metal anode materials obtained in Examples 1-4 were tested for cycle time, surface energy, and overpotential. The test results are shown in the table below: Table 2. Results of Limitation Index and Cycle Time
[0089] Verification of technical effectiveness and / or analysis of technical problem solving The ammonium fluoroborate used in this invention hydrolyzes in water to produce hydrofluoric acid (HF) and boric acid (H3BO3), which then react with Mg... 2+ By self-assembling, a network of nanosheets rich in inorganic components such as magnesium fluoride and magnesium borate is formed on the surface of magnesium metal, which has properties such as electronic insulation, ionic insulation and mechanical stability.
[0090] Simultaneously, treating the magnesium anode with HF, H3BO3, and a mixture thereof at the same pH for the same duration yielded morphological characteristics similar to those obtained with NH4BF4 solution treatment. More importantly, compared to the untreated magnesium anode, all exhibited superior electrochemical performance.
[0091] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.
Claims
1. A method for modifying the surface morphology of a magnesium metal anode, characterized in that, Including the following steps: (1) Remove the oxide layer from the magnesium metal anode to obtain the treated magnesium metal; (2) Dissolve ammonium fluoroborate in water to obtain an ammonium fluoroborate solution; (3) The magnesium metal obtained in step (1) is reacted with the ammonium fluoroborate solution obtained in step (2) to obtain the modified magnesium metal anode with the modified surface morphology.
2. The negative electrode modification method according to claim 1, characterized in that, The magnesium metal negative electrode is selected from at least one of sheet, foil, block, and wire; preferably at least one of sheet and foil; more preferably foil. The shape of the foil-shaped magnesium metal negative electrode is selected from at least one of circular, rectangular, and porous shapes; preferably circular; more preferably circular with a diameter of 1 cm; The method for removing the oxide layer is selected from at least one of physical removal, acid etching, alkaline cleaning, and organic solvent soaking; preferably at least one of physical removal and acid etching; more preferably physical removal. Preferably, the physical removal includes mechanical grinding and mechanical polishing. More preferably, the grit of the sandpaper used for mechanical polishing is selected from 400-5000 grit; even more preferably, it is 600-2000 grit; most preferably, the mechanical polishing is performed by sequentially polishing with 600 grit, 1000 grit, and 2000 grit sandpaper. More preferably, the mechanical polishing method is selected from at least one of wet polishing, dry polishing, metallographic polishing machine polishing, and ultrasonic-assisted mechanical polishing; even more preferably, the mechanical polishing method is metallographic polishing machine polishing.
3. The negative electrode modification method according to claim 1, characterized in that, The water is selected from at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; preferably at least one of purified water, deionized water, and distilled water; more preferably deionized water. Preferably, the concentration of the ammonium fluoroborate solution obtained in step (2) is 1wt%-5wt%; more preferably 1wt%-3wt%; and even more preferably 2wt%.
4. The negative electrode modification method according to claim 1, characterized in that, The reaction temperature in step (3) is 10-30℃; preferably 25℃. The reaction time in step (3) is 1-10 min; preferably 5 min. Preferably, the reaction in step (3) is followed by a washing and drying step; More preferably, the solvent used for cleaning is water; even more preferably, the water is selected from at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; most preferably, it is deionized water. More preferably, the drying method is selected from at least one of freeze drying, spray drying, oven drying, air drying, blow drying, natural drying, and vacuum drying; even more preferably, the drying method is oven drying; even more preferably, the drying temperature is 30-60℃; most preferably 40℃; even more preferably, the drying time is 1-3h; most preferably 2h.
5. A magnesium metal anode with modified surface morphology prepared by the anode modification method according to any one of claims 1-4, characterized in that, A uniform and continuous insulating nanosheet network is formed on the surface of the magnesium metal anode, with an average pore size of less than 125 nm. Preferably, the average pore size is less than 90 nm; more preferably less than 80 nm; and even more preferably 68.95 nm.
6. The application of the negative electrode modification method according to any one of claims 1-4 in magnesium metal battery materials.
7. A method for modifying the surface morphology of a magnesium metal anode, characterized in that, Including the following steps: (1) Remove the oxide layer from the magnesium metal anode to obtain the treated magnesium metal; (2) Dissolve HF or H3BO3 in water to obtain a reaction solution; (3) The magnesium metal obtained in step (1) is reacted with the reaction solution obtained in step (2) to obtain the modified magnesium metal anode with the modified surface morphology.
8. The negative electrode modification method according to claim 7, characterized in that, The magnesium metal negative electrode is selected from at least one of sheet, foil, block, and wire; preferably at least one of sheet and foil; more preferably foil. The shape of the foil-shaped magnesium metal negative electrode is selected from at least one of circular, rectangular, and porous shapes; preferably circular; more preferably circular with a diameter of 1 cm; The method for removing the oxide layer is selected from at least one of physical removal, acid etching, alkaline cleaning, and organic solvent soaking; preferably at least one of physical removal and acid etching; more preferably physical removal. Preferably, the physical removal includes mechanical grinding and mechanical polishing. More preferably, the grit of the sandpaper used for mechanical polishing is selected from 400-5000 grit; even more preferably, it is 600-2000 grit; most preferably, the mechanical polishing is performed by sequentially polishing with 600 grit, 1000 grit, and 2000 grit sandpaper. More preferably, the mechanical polishing method is selected from at least one of wet polishing, dry polishing, metallographic polishing machine polishing, and ultrasonic-assisted mechanical polishing; even more preferably, it is metallographic polishing machine polishing.
9. The negative electrode modification method according to claim 7, characterized in that, The water is selected from at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; preferably at least one of purified water, deionized water, and distilled water; more preferably deionized water. The concentration of the reaction solution obtained in step (2) is 1wt%-5wt%; preferably 1wt%-3wt%; more preferably 2wt%.
10. The negative electrode modification method according to claim 7, characterized in that, The reaction temperature in step (3) is 10-30℃; preferably 25℃. The reaction time in step (3) is 1-10 min; preferably 5 min. Preferably, the reaction in step (3) is followed by a washing and drying step; More preferably, the solvent used for cleaning is water; even more preferably, the water is selected from at least one of purified water, deionized water, mineral water, distilled water, drinking water, and ultrapure water; most preferably, the water is deionized water. More preferably, the drying method is selected from at least one of freeze drying, spray drying, oven drying, air drying, blow drying, natural drying, and vacuum drying; even more preferably, the drying method is oven drying. More preferably, the drying temperature is 30-60℃; most preferably, it is 40℃. More preferably, the drying time is 1-3 hours; most preferably 2 hours.
Citation Information
Patent Citations
MXene modification layer modified magnesium metal negative electrode, preparation method thereof and magnesium metal battery
CN117727879A
Fluoride ion battery, negative electrode active material for fluoride ion battery, and method for producing same
CN118693250A
MXene ZIF-67 composite coating on surface of negative electrode of magnesium battery and preparation method of MXene ZIF-67 composite coating
CN119101972A